miR-27a-5p, miR-21-5p, miR-1246 and miR-4508: a candidate microRNA signature in the protection and regulation of viral infection in mild COVID-19 - Malena Gajate-Arenas; Candela Sirvent-Blanco; Omar García-Pérez; Angélica Domínguez-de-Barros; José E. Piñero; Jacob Lorenzo-Morales; Elizabeth Córdoba-Lanús (Molecular Medicine)
Abstract MicroRNAs (miRNAs) are gene regulators essential for cell homeostasis, their alteration is related to a pathological state, including infectious diseases like COVID-19. Identifying an altered profile of circulating miRNAs in mild COVID-19 may enhance our knowledge of the pathogenesis of SARS-CoV-2 and the range of clinical phenotypes. In the present study, a miRNA screening was performed by Next Generation Sequencing (NGS), and the expression levels of 13 resulting miRNAs were validated through RT-qPCR in the serum of 40 mild cases compared to 29 non-infected individuals. An in-silico analysis was performed to detect target genes and their related pathways. From the validated miRNAs, miR-1246 (p < 0.001), miR-423-5p (p < 0.001), miR-21-5p (p = 0.005), miR-146a-5p (p < 0.001), miR-4508 (p = 0.001), miR-629-5p (p < 0.001), and miR-210-3p (p = 0.002) were found downregulated in infected individuals. Only miR-27a-5p was overexpressed in subjects with COVID-19 (p = 0.013) and associated with SARS-CoV-2 infection (p = 0.010). The KEGG pathways and GO analysis revealed that the differentially expressed miRNAs were related to viral processes or immunological pathways: miR-27a-5p acts on the TGF-beta pathway; miR-21-5p targets SMAD7, which is associated with the inflammatory response in the lung; miR-1246 acts on p53 pathway; and miR-4508 acts on ICAM2. In conclusion, the most relevant miRNAs, miR-27a-5p and miR-21-5p, were differently expressed in mild forms of COVID-19. The higher expression of miR-27a-5p observed in mild COVID-19 cases may suggest a protective effect against severe forms of the disease. Reduced expression of miR-21-5p may prevent pulmonary inflammation and the progression of fibrosis. The downregulation of miR-1246 and miR-4508 in mild COVID-19 cases may conduct the correct control of the infection. Moreover, miR-423-5p might be a suitable biomarker in the early stages of SARS-CoV-2 infection.